Determinants of apple post harvest losses in Paktia, Afghanistan - Amanullah, Amin (2020)
Apples are an important fruit and ranked third after grapes and almond in Afghanistan. Afghan apples are among the crunchiest, sweetest, and largest in the region. Losses in agriculture sector in Paktia province are largely due to the extremely perishable quality of the produce and poor management of post-harvest activities. This calls for a wellorganized post-harvest management on the part of farmers supported by strong infrastructure facilities for proper production activities. Therefore, the aim of this study was to survey the post-harvest losses of apples in Paktia, Afghanistan. The specific objectives of the study were to identify the post-harvest activities, losses and constraints among apple growers, to explore the association between socio-demographic and postharvest losses, to identify the factors affecting post-harvest losses among apple growers and to determine the most influential factors that affect the post-harvest losses of apples. A quantitative research design was chosen for this study. The three districts, namely Gardiz, Saidkaram and Ahmad Aba, were selected purposively as they represent the top three apple producing districts of Paktia province. A registered list of apples growers and villages were obtained from the Department of Agriculture, Irrigation and Livestock of Paktia province where 26 villages were chosen out of 52 villages. From 52 villages, a total of 923 apples growers were identified and 279 apples growers were then selected from 26 villages based on systematic random sampling technique. Primary data were collected using designed questionnaires via face-to-face structured interviews. Data collected were then analyzed using descriptive analysis, chi-square analysis, factor analysis and multiple linear regression analysis. The finding of descriptive analysis showed that among all the post-harvest activities based on the percentage ranking, all apples growers (100%) were involved in the marketing of apples that were in search of direct or indirect channels to sell their products in order to reduce the losses. Meanwhile, total postharvest losses of apples during all post-harvest activities were estimated around 34.92%. Storage was the major losses factor for apple growers that they lose 8.91% produce. Accordingly, the major constraint of production was spurious pesticide and fungicide (96.7%), while the major marketing constraints was lack of standard storage or cold storage (98.5%) and finally, unstable political relations with neighboring countries (100%) was the main constraint of policy. The findings on the chi-square analysis showed that education level (P=0.046), farm size (P=0.000), farm experience (P=0.019), yield (P=0.000) have significant association with post-harvest losses. Moreover, the factor analysis results revealed seven factors that influenced post-harvest losses of apples, namely harvesting, sorting, grading, packaging, storage, transportation and marketing. Therefore, establishing proper storages and packaging facilities will reduce their losses that will ease their effort in finding a better market for their products during the different season of the year. Also, sorting and grading will raise the value of apple products for a better marketing. Both road transport and transportation system should be improved upon so as to reduce the losses of apple production. Based on the multiple regression analysis, farm experience, yield, harvesting, grading, packaging, storage and transportation had a negative and significant relationship with post-harvest losses of apples. Among these factors, grading and storage were an extremely important and has the greatest influence on post-harvest losses. The adequate storage capacity, cold storage availability and facilities of warehousing are essential requirements to reduce wastage and maintain the quality of the apple products. Findings of this study can assist the government and NGO in developing the right policy and agricultural development of apple production in Afghanistan that will benefit the stakeholders in the apples industry.